Carving your destiny in academia as a “lecturer” and a “mother” - Soubakeavathi, Rethinasamy (Routledge, 2023)
Hidden within the single-word job title “lecturer” is a long list of multi-layered responsibilities. For a woman who is a lecturer, possibly added to this long list is the undefinable crucial “job” packaged into an oversimplified single word – “Mother.” In this autoethnography, the author provides a comprehensive view of a woman’s life in academia by illustrating how she navigates through the demanding responsibilities of a university lecturer and carves her destiny out of the academic world while endeavouring to be the best possible mother. The author shares the attractive opportunities and the real challenges faced while pursuing a PhD. This is followed by an illustration of the challenges experienced in holding major administrative positions and how a display of commitment increases visibility and bolsters research networking. This chapter also unfolds the secrets to maintaining career-life balance by developing the support system that enables a woman in academia to weave her career trajectory.